Nursing as a Mother and Wife in the Covid-19 Period - Gül, Dilek; Uluocak, Şeref (Fırat Üniversitesi, 2025)
Within the scope of this study, the disadvantages experienced by nurses as mothers and wives during the pandemic period and the emotional concerns caused by these disadvantages are emphasized. In this sense, it is aimed to examine many problem areas related to both their professional responsibilities and their roles in the family, with the effect of emotional factors caused by the risks faced by nurses in the period in question. Nurses; As mothers, wives and a healthcare worker, they encounter many stress factors in their daily and professional lives. The problematic question of whether the measures that can be taken regarding the anxiety situations experienced by nurses due to stress factors are structured within the health system and on the axis of health policies is discussed. In this context, one of the main assumptions of the research is based on the necessity of restructuring the working environment in order to eliminate the disadvantages experienced by nurses, and in this sense, nurses should be supported psycho-socially as well as in many socio-cultural, economic, and political areas. The research was carried out within the framework of in-depth interviews as a data collection technique suitable for qualitative data analysis within the framework of the grounded theory design. The sample of the study consists of 24 nurses working at Çanakkale 18 Mart University Research and Application Hospital. The obtained data were analyzed in a critical realist methodological framework in accordance with the theory design based on the MAXQDA program. From a critical realist methodological perspective, the roles of nurses working in the Covid-19 period were primarily subjected to a meta-theoretical inquiry within the framework of the ontological and epistemological assumptions of critical realism, and reasoning, coding and analysis processes based on abduction and retroduction were carried out. Among the most basic findings of the research, it is emphasized that the participants were worried about the fear of infecting their family members as mothers, wives and nurses during the Covid-19 period, and that they had difficulty in balance/equalizing both their professional roles and their roles in the family in this process. In addition, it was observed that while the participants fulfilled their professional responsibilities, they also experienced the stigmatization process and therefore the feeling of guilt because they were seen as possible carriers of the Covid-19 disease. In addition to the psycho-training that can be created on the axis of nurses who have both psychological and physical reflections of the risk factors that occur during this process, it is important to provide appropriate working conditions.

Bu çalışma kapsamında, sağlık çalışanları olarak hemşirelerin anne ve eş olarak pandemi dönemindeki yaşadıkları dezavantajlar ve bu dezavantajların oluşturduğu duygusal kaygılar üzerinde durulmaktadır. Bu anlamda çalışma ekseninde hemşirelerin söz konusu dönemde karşılaştıkları riskler sebebiyle oluşan duygusal faktörlerin etkisi ile hem mesleki sorumlulukları hem de aile içerisinde var olan rollerine ilişkin pek çok sorun alanının incelenmesi amaçlanmaktadır. Hemşireler; anne, eş ve bir sağlık çalışanı olarak gündelik ve mesleki yaşamları içerisinde pek çok stres faktörü ile karşılaşmaktadırlar. Hemşirelerin stres faktörleri sebebi ile yaşadıkları kaygı durumlarına ilişkin alınabilecek önlemlerin, sağlık sistemi içerisinde ve sağlık politikaları ekseninde ne ölçüde yapılandırılıp yapılandırılmadığı problematiği ele alınmaktadır. Bu bağlamda araştırmanın temel varsayımlarından biri, hemşirelerin yaşadıkları dezavantajların giderilmesi ekseninde çalışma ortamının yeniden yapılandırılması ve bu anlamda hemşirelerin sosyo-kültürel, ekonomik ve politik pek çok alanın yanı sıra psiko-sosyal olarak da desteklenmelerinin gerekliliğine dayanmaktadır. Araştırma, temellendirilmiş kuram deseni çerçevesinde, nitel veri analizine uygun bir veri toplama tekniği olarak derinlemesine görüşmeler çerçevesinde gerçekleştirilmiştir. Çalışmanın örneklemini Çanakkale 18 Mart Üniversitesi Araştırma ve Uygulama Hastanesi’nde görev yapan 24 hemşire oluşturmaktadır. Elde edilen veriler MAXQDA programı ile temellendirilmiş kuram desenine uygun olarak eleştirel realist bir metodolojik çerçevede analiz edilmiştir. Eleştirel realist metodolojik bir perspektiften Covid-19 döneminde çalışan hemşirelerin rolleri, eleştirel realizmin ontolojik ve epistemolojik varsayımları çerçevesinde öncelikli olarak meta-teorik bir sorgulamaya tabi tutulmuş, abdüksiyona ve retrodüksiyona dayalı akıl yürütme, kodlama ve analiz süreçleri gerçekleştirilmiştir. Araştırmanın en temel bulguları arasında, katılımcıların Covid-19 döneminde anne, eş ve bir hemşire olarak aile üyelerine bu hastalığı bulaştırma korkusundan dolayı kaygılandıkları ve gerek mesleki rollerini gerekse de aile içerisindeki rollerini bu süreçte dengeleme/eşitleme konusunda zorluk yaşadıkları vurgusu yer almaktadır. Bunun yanı sıra katılımcıların mesleki sorumluluklarını yerine getirirken aynı zamanda Covid-19 hastalığının muhtemel taşıyıcısı olarak görüldüklerinden dolayı damgalanma sürecini ve bu nedenle oluşan suçluluk duygusunu yaşadıkları da gözlemlenmiştir. Bu süreç içerisinde oluşan risk faktörlerinin hem psikolojik hem bedensel yansımalarını taşıyan hemşireler ekseninde oluşturulabilecek psiko-eğitimlerin yanı sıra uygun çalışma koşullarının sağlanması önem taşımaktadır.
COVID-19 DÖNEMİNDE ANNE VE EŞ OLARAK HEMŞİRELİK
Keywords: Gender and Politics; Toplumsal Cinsiyet ve Siyaset